The Effectiveness of Monetary, Macroprudential, and Microprudential Policies on Financial Stability in Indonesia During and Post-COVID-19 - Veronika, Yurike; Efendi, Bakhtiar (Golden Ratio of Data in Summary, 2025)
This study examines the impact of monetary policy (inflation and money supply), macroprudential (minimum reserve requirements and net open position), and microprudential (Capital Adequacy Ratio and Non-Performing Loan) on Indonesia's financial system stability, proxied by the exchange rate, during and post COVID-19 pandemic (2019-2024). The study employs secondary monthly time-series data and applies the Autoregressive Distributed Lag (ARDL) approach to analyze short and long-term relationships. The Wald Test is used to compare policy effectiveness across the two periods. The results indicate that Money Supply (M2), Net Open Position (NOP), and Non-Performing Loans (NPL) significantly affect the exchange rate in the long run. In contrast, Inflation, Minimum Reserve Requirements, and the Capital Adequacy Ratio (CAR) do not significantly affect. These findings suggest that M2, NOP, and NPL are the most reliable indicators for predicting Indonesia's post-pandemic financial stability. From a policy perspective, the study underscores the importance of stronger coordination among monetary, macroprudential, and microprudential policies to enhance the financial system's resilience against future shocks.